REVIEW OF INDONESIAN NATIONAL WORK COMPETENCY STANDARDS FROM THE PROFESSIONAL STANDARDIZATION NATIONAL AGENCY IN CREATIVE MEDIA STANDARD POLYTECHNICS JAKARTA - Zalzulifa Zalzulifa; Nasaruddin Nasaruddin; Purnomo Ananto (Jurnal Ilmiah Publipreneur, 2019)
The research objective is to describe and interpret the extent to which the level of requirements for the Indonesian National Work Competency Standards (SKKNI) from the National Professional Standardization Agency (BNSP) applied to the State Polytechnic of Creative Media (PoliMedia) ". The research method used is quantitative research methods with the approach used is descriptive, namely a strategy that aims to describe a phenomenon and its characteristics by collecting data in the form of numbers. The population is only 19 people, so the sample used is a total sample of 19 people, so this research is called population research. The collection technique used a closed questionnaire, in which 19 practitioners of the book publishing industry answered questions (questionnaires) with four answer choices, namely; unnecessary scores (1), need not scores (2), need scores (3) and, urgently need scores (4). Questions regarding competency units as guidelines for the preparation of SKKNI from the National Professional Standardization Agency (BNSP) must be applied to the State Polytechnic of Creative Media (PoliMedia). Analysis of the research data was descriptive analysis with the help of SPSS 22.00. The results of the research as a whole, the level of the need for the competency unit as a guide for the preparation of the National Agency for Professional Standardization (BNSP) applied to the Creative Media State Polytechnic (PoliMedia) was 86.8% of the expected 100%.